Effects of short-period exercise training and orlistat therapy on body composition and maximal power production capacity in obese patients - Colak, R; Ozcelik, O (Acad Sciences Czech Republic, Inst Physiology, 2004)
We examined the effects of weight loss induced by diet-orlistat (DO) and diet-orlistat combined with exercise (DOE) on maximal work rate production (W-max) capacity in obese patients. Total of 24 obese patients were involved in this study. Twelve of them were subjected to DO therapy only and the remaining 12 patients participated in a regular aerobic exercise-training program in addition to DO therapy (DOE). Each patient performed two incremental ramp exercise tests up to exhaustion using an electromagnetically-braked cycle ergometer: one at the onset and one at the end of the 4th week. DOE therapy caused a significant decrease in total body weight: 101.5 +/- 17.4 kg (basal) vs 96.3 +/- 17.3 kg (4 wk) associated with a significant decrease in body fat mass: 45.0 +/- 10.5 kg (basal) vs 40.9 +/- 9.8 kg (4 wk). DO therapy also resulted in a significant decrease of total body weight 94.9 +/- 14.9 kg (basal) vs 91.6 +/- 13.5 kg (4 wk) associated with small but significant decreases in body fat mass: 37.7 +/- 5.6 kg (basal) to 36.0 +/- 6.2 kg (4 wk). Weight reduction achieved during DO therapy was not associated with increased W-max capacity: 106 +/- 32 W (basal) vs 106 +/- 33 W (4 wk), while DOE therapy resulted in a markedly increased W-max capacity: 109 +/- 39 W (basal) vs 138 +/- 30 W (4 wk). DO therapy combined with aerobic exercise training resulted in a significant reduction of fat mass tissue and markedly improved the aerobic fitness and W-max capacities of obese patients. Considering this improvement within such a short period, physicians should consider applying an aerobic exercise-training program to sedentary obese patients for improving their physical fitness and thereby reduce the negative outcomes of obesity.
Keywords: obesity; body mass index; aerobic exercise intensity